(untitled) (Research, Society and Development, 2020)
The development of new products or services can be considered one of the main processes to guarantee the competitiveness of a company in the environment in which it operates. However, it is necessary that this development and supply process be well planned and structured in order to respond to the needs of the consumer market. In this sense, marketing plays a valuable role in seeking to reveal and understand information regarding potential customers, with the purpose of ensuring the success of the new service or product, as well as its acceptance and dissemination. In this context, marketing communication stands out, an inseparable tool from the reality of organizations, responsible for transmitting the competitive advantages of the organization, highlight the main attributes related to the product or service and assist in the construction and maintenance of the relationship with customers. Thus, this study aims to develop and implement marketing communication strategies for the launch of an event with a career focus in the central region of Rio Grande do Sul. The method used was a qualitative and quantitative action research. The communication strategies developed can be summarized in five groups: Advertising Strategies, Sponsorship, Promotion, Direct Marketing and Digital Marketing. Among these, the ones that were most effective were the Digital Marketing strategies, represented by dissemination via social networks, mainly Facebook and Advertising strategy, consisting of visits to universities; while radio advertising proved to be less effective.